Screening of selected Indonesian plants for antiplatelet activity - Nanang Fakhrudin; Fatiya Farih Mufinnah; Muhammad Faishal Husni; Arief Eka Wardana; Eradhian Irma Wulandari; Arbie Ristanto Putra; Djoko Santosa; Arief Nurrochmad; Subagus Wahyuono (Society for Indonesian Biodiversity, 2021)
Abstract. Fakhrudin N, Mufinnah FF, Husni MF, Wardana AE, Wulandari EI, Putra AR, Santoso D, Nurrichmad A, Wahyunono S. 2021. Screening of selected Indonesian plants for antiplatelet activity. Biodiversitas 22: 5268-5273. Cardiovascular diseases remain the leading cause of death worldwide. Platelet aggregation plays a crucial role in the development of cardiovascular diseases. Thus, the discovery of bioactive compounds targeting platelet aggregation is a promising approach for combating cardiovascular diseases. Indonesia has plants diversity with the potential to be developed as antiplatelet agents. Thus, this study was aimed to identify the antiplatelet potential of selected Indonesian plant extracts. The plant extracts (100 µg mL-1) were evaluated for their antiplatelet activity in CaCl2-induced platelet aggregation in 96-well plates. In an aggregometer, the active extracts were further evaluated in adenosine diphosphate (ADP)-induced platelet aggregation. The antiplatelet agents, aspirin, and ticagrelor were used as reference drugs in the respective screening assays. Of the 139 tested extracts, ten demonstrated antiplatelet activity in CaCl2-induced platelet aggregation. The evaluation of the ten active extracts in ADP-induced platelet aggregation revealed four active extracts. The most active extract was the methanol extract of Cinnamomum sintoc bark, followed by the methanol extract of Leea aequata leaf, and the dichloromethane and methanol extracts of Physalis angulata petal with moderate activities. This study provides essential scientific evidence for the development of antiplatelet agents from plant origins.